The village preacher "Lebai Kampung": Shaykh (Dr.) Muhammad Uthman El-Muhammady - Hassan @ Mohamed, Nor Jana; Muhammad Uthman El-Muhammady, Asma; Dargan, Gary; A. Rahim, Fadzillah; Abdul Mutalib, Marina Munira; Bashir, Aamir; Wong Suk Ting, Aidah; Atundal Hajdari, Sevgi (Office for Islamisation, CENTRIS, IIUM, 2021)
The Village Preacher is the outcome of a special project by al-Futuwwah, the Students' Association of ISTAC of the 2012-2013, 2013-2014 and 2014-2015 adacemic years, in commemoration of the beloved and dearly missed teacher and murabbi. In him, his students of all walks of life and his contemporaries found one of the brightest stars that twinkled with wisdom, humility, erudition and a guiding light. This special book is divided into two parts. Part One consists of anecdotes on the life of al-marhum, written by his daughter and students, and a number of his photographs. Part Two comprises of actual assignments, tests and final papers by his students, submitted to and graded by him - a select sampling from stacks and bundles of papers retrieved from his collection at his office and at his residence in ISTAC and in Pasir Mas Kelantan. Indeed, in him we see an exemplary beacon for us all. This book presents none, but a glimpse of this beacon.